APPLICATION OF SHAPE MEMORY ALLOY IN REINFORCED CONCRETE STRUCTURE - MD DESA, MUHAMMAD AMIN (IRC, 2016)
The study on application of Shape Memory Alloys (SMA) in had been done previously with different methods. This new material have the unique ability to sustain large deformations and returned to their original shape upon stress applied for Superelastic SMA or by heating the SMA for Shape Memory Effect Abdulridha, Palermo, Foo and Vecchio(2013)to further analyse the performance towards the application of the SMA bars in reinforced concrete structure as a to help enhance reinforce concrete into resisting lateral load and towards providing more valuable information for prediction of the performance behaviour of SMAs towards modern structure. This research is to compare the performance between segmental column reinforced with Mild Steel, Superelastic SMA and Niti Martensitic SMA longitudinal bars. The bars are used are longitudinal bars located at bottom of the column to resist the lateral deflection and help in gap closing effect.